2014
DOI: 10.18632/oncotarget.2344
|View full text |Cite
|
Sign up to set email alerts
|

Diacylglycerol kinase α promotes 3D cancer cell growth and limits drug sensitivity through functional interaction with Src

Abstract: Diacylglycerol kinase (DGK)α converts diacylglycerol to phosphatidic acid. This lipid kinase sustains survival, migration and invasion of tumor cells, with no effect over untransformed cells, suggesting its potential as a cancer-specific target. Nonetheless the mechanisms that underlie DGKα specific contribution to cancer survival have not been elucidated. Using three-dimensional (3D) colon and breast cancer cell cultures, we demonstrate that DGKα upregulation is part of the transcriptional program that result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
51
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(55 citation statements)
references
References 72 publications
(97 reference statements)
3
51
0
Order By: Relevance
“…We also reported that DGK ␣ -specifi c siRNA attenuated the proliferation of hepatocellular carcinoma ( 9 ) and induced apoptosis in melanoma cells ( 10 ). Supporting our results, Torres-Ayuso et al ( 40 ) also demonstrated that the growth of colon and breast cancer cell lines was effect of CU-3 ( Fig. 11 ), indicating that CU-3 and DGK ␣ -siRNA inhibit the same target, DGK ␣ .…”
Section: Enhancement Of the Il-2 Production By Cu-3supporting
confidence: 87%
See 1 more Smart Citation
“…We also reported that DGK ␣ -specifi c siRNA attenuated the proliferation of hepatocellular carcinoma ( 9 ) and induced apoptosis in melanoma cells ( 10 ). Supporting our results, Torres-Ayuso et al ( 40 ) also demonstrated that the growth of colon and breast cancer cell lines was effect of CU-3 ( Fig. 11 ), indicating that CU-3 and DGK ␣ -siRNA inhibit the same target, DGK ␣ .…”
Section: Enhancement Of the Il-2 Production By Cu-3supporting
confidence: 87%
“…Therefore, our current results encourage us to identify and develop specifi c inhibitors/activators against every DGK isozyme that can be effective regulators and drugs against a wide variety of physiological events and diseases ( 4 ). For example, DGK ␣ : cancer cell growth ( 9,10,37,40 ), angiogenesis ( 41 ), T-cell proliferation ( 45 ), and T-cell anergy ( 12, 13 ); DGK ␤ : bipolar disorder ( 46, 47 ); DGK ␥ : actin reorganization ( 19 ), allergy ( 48 ), and insulin secretion ( 49 ); DGK ␦ : epidermal growth factor receptor signaling ( 50 ) and type 2 diabetes ( 51, 52 ); DGK : epidermal growth factor receptor signaling ( 53 ), lung cancer ( 54 ), bipolar disorder ( 55,56 ), unipolar depression ( 56 ), and attention-defi cit/hyperactivity disorder ( 56 ); DGK : hypospadias ( 57 ); DGK : seizure susceptibility/ long-term potentiation ( 58 ) and Huntington's disease ( 59 ); DGK : cell growth ( 60 ), T-cell receptor response ( 61 ), and brain ischemia ( 62 ); DGK : Ras signaling ( 63 ); and DGK : Parkinson's disease ( 64 ) and bile acid signaling ( 65 ).…”
Section: Discussionmentioning
confidence: 80%
“…The oncogenic Src kinase has been found to phosphorylate DGKα to promote its activity (6, 35), but whether Src inhibitors such as dasatinib have a significant effect on DGKα activity remains to be tested. Src may also lie downstream of DGKα, with Src and DGKα comprising a positive feedback loop (36). The Abl oncogene product also modulates DGKα, through regulation of its export from the nucleus (37).…”
Section: Introductionmentioning
confidence: 99%
“…Surprisingly, both DGKα and ζ also play a key role in cancer-cell survival, acting at either the plasma membrane, intracellular organelles, or the nucleus (Baldanzi et al, 2011b; Filigheddu et al, 2011; Dominguez et al, 2013; Kefas et al, 2013; Tanaka et al, 2013; Torres-Ayuso et al, 2014, 2015; Poli et al, 2016). However, the signaling pathways that converts PA and DAG at cell membranes in cell survival signaling are poorly understood, as few PA-regulated proteins are linked to the control of apoptosis and the cell cycle.…”
Section: Dgks In Directional Migrationmentioning
confidence: 99%